2008
DOI: 10.1124/dmd.108.024208
|View full text |Cite
|
Sign up to set email alerts
|

Close Association of UGT1A9 IVS1+399C>T with UGT1A1*28, *6, or *60 Haplotype and Its Apparent Influence on 7-Ethyl-10-hydroxycamptothecin (SN-38) Glucuronidation in Japanese

Abstract: ABSTRACT:The anticancer prodrug, irinotecan, is converted to its active form 7-ethyl-10-hydroxycamptothecin (SN-38) by carboxylesterases, and SN-38 is inactivated by UDP-glucuronosyltransferase (UGT)1A1-mediated glucuronidation. UGT1A9 also mediates this reaction. In a recent study, it was reported that the UGT1A9 IVS1؉399 (I399)C>T polymorphism is associated with increased SN-38 glucuronidation both in vitro and in vivo. However, its role in UGT1A9 expression levels and activity is controversial. Thus, we eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 16 publications
1
15
0
1
Order By: Relevance
“…The allele frequencies of CYP2B6 G516T and UGT1A9 I399C>T mutations identified in our study were 23% and 62%, respectively. These frequencies are similar to past reports of approximately 20% and 64% of the allele frequencies of Japanese past reports and UGT1A9 I399C>T mutations 9) , respectively. In our study, no significant differences were found between genetic polymorphisms and waking times after propofol anesthesia.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The allele frequencies of CYP2B6 G516T and UGT1A9 I399C>T mutations identified in our study were 23% and 62%, respectively. These frequencies are similar to past reports of approximately 20% and 64% of the allele frequencies of Japanese past reports and UGT1A9 I399C>T mutations 9) , respectively. In our study, no significant differences were found between genetic polymorphisms and waking times after propofol anesthesia.…”
Section: Discussionsupporting
confidence: 79%
“…Propofol is metabolized by its hydroxylation by CYP2B6 and by its glucuronidation by UGT1A9, resulting in propofol changing into a conjugated compound that has no anesthetic activity and is excreted in urine, as with other metabolites 7) . Genetic polymorphisms in CYP2B6 and UGT1A9 have been reported, along with their allele frequency in the Japanese population [8][9][10] . Several studies have shown that the allele frequency of the G516T mutation of CYP2B6 was approximately 20%, and the variation among genetic polymorphisms decreased the enzyme activity of CYP2B6 8) [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…As expected, the relative frequencies for these alleles are intermediate in the admixed samples, and the variants are present in frequencies that are proportional to the relative admixture proportions. In the case of UGT1A1 , the frequencies of variants that have been associated with irinotecan response (−3156G>A/−349C>T and UGT1A1*60 ) [32], [33], [34], [35] are also higher in European than Native American and West African populations. The consistent higher frequencies of the functional CYP2D6 and UGT1A1 alleles/haplotypes observed in Europeans vs. the other two populations are probably the result of ascertainment bias, because most of the studies exploring variants with potentially functional effects have been carried out in European populations.…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, UGT1A9 Ϫ 118T 9 >T 10 and 1399C>T genetic variations were found in high linkage disequilibrium in the present study ( Fig. 3 ) and among Asians, but not Caucasians ( 29,30 ).…”
Section: Discussionmentioning
confidence: 68%